The Effect of Social Interaction, Social Media on Brand Equity and Purchase Intention of Starbucks Brand - Arifin Djakasaputra; M.Tony Nawawi (International Journal of Management Science and Application, 2025)
Building brand equity is extremely important because it serves the company's identity and is one of the main factors in consumer decision-making when purchasing a product. In the digital age, social interaction and social media are key factors that determine consumer perceptions of a brand. This study aims to examine the influence of social interaction and social media on brand equity and its impact on consumer purchase intention, using Starbucks in Jakarta as a case study. This study uses a non-probability sampling method with a purposive sampling technique on 120 respondents who are Starbucks customers. The research instrument was measured using a Likert scale with several indicators for the social interaction, social media, brand equity, and purchase intention variables. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The research results indicate that social media has a positive and significant influence on brand equity, and social interaction also has a positive and significant influence on brand equity, while brand equity is proven to have a positive and significant influence on consumer purchase intention. This finding confirms the importance of social media-based marketing strategies and social interaction in enhancing brand equity, which can ultimately drive consumer purchase intention. The implications of this research contribute theoretically to the digital marketing literature and have practical implications for companies in designing more effective brand communication strategies.